Cardioprotective effect of virgin coconut oil in heated palm oil diet-induced hypertensive rats - Kamisah Y.; Periyah V.; Lee K.T.; Noor-Izwan N.; Nurul-Hamizah A.; Subermaniam K.; Jaarin K.; Azman A.; Faizah O.; Qodriyah H.M.S.; Nurul Iman Badlishah Sham (Taylor and Francis Ltd, 2024)
Indexed by SCOPUS/WOS